Simulation of the combustion process for a CI hydrogen engine in an argon-oxygen atmosphere. (14th June 2018) - Hafiz, Nik Muhammad; Mansor, Mohd Radzi Abu; Wan Mahmood, Wan Mohd Faizal
Abstract: Hydrogen combustion in a noble gas atmosphere increases the combustion chamber temperature, and the high specific heat ratio of the gas increases the thermal efficiency. In this study, nitrogen was replaced by argon as the intake air along with pure oxygen to supply the engine. The objectives of this study are to determine the effects of different engine parameters on combustion and to analyse the emissions from hydrogen combustion in an argon-oxygen atmosphere. This research was conducted through simulations using CONVERGE 2.2.0 software, and the YANMAR engine NF19SK model was used to determine the basic parameters. Changing the injector location affects the pressure and temperature in the combustion chamber. With increasing compression ratio, the pressure increases more rapidly than the temperature. However, combustion at high compression ratios decreases the maximum heat release rate and increases the combustion duration. Hydrogen combustion at ambient temperatures below 1200 K follows the Arrhenius equation. Highlights: The hydrogen combustion characteristics were improved with a high specific ratio of argon in the oxygen atmosphere. Parameter modification by changing the injector location to the middle of the cylinder slightly improved combustion. With increasing compression ratio, pressure increased more rapidly than temperature, while the heat release rate decreased. Late injection timing is preferred to avoid abnormal burning and ensure that maximum pressure is not reached prematurely. Emissions from hydrogen combustion in an argon-oxygen atmosphere were composed of 79% Ar, 19% O2 and 2% H2 O.